Implementasi Kebijakan Akomodasi Yang Layak Untuk Peserta Didik Penyandang Disabilitas Di Universitas Muhammadiyah Jakarta - Githa Putri Rengganis; Dini Gandini Purbaningrum (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
This article discusses the implementation of adequate accommodation policies for students with disabilities at the University of Muhammadiyah Jakarta. The purpose of this study is to determine the implementation of adequate accommodation policies for students with disabilities at the University of Muhammadiyah Jakarta. The research method used is a descriptive method with a qualitative approach and uses the theory of Edward III. The result of this study is that the University of Muhammadiyah Jakarta has implemented the regulation, but it has not run optimally because there are several obstacles such as infrastructure that has existed long before the entry of students with disabilities, limited budget devoted to disability infrastructure, and there has been no special training for staff / employees so that it has not produced excellent service for students with disabilities.